Improvement of railway topographic plans updating technologies - Sužiedelytė-Visockienė, Jūratė (Transport, 2006)
Peculiar technologies on the update of topographic map linear objects to scale 1:500–1:2000 are presented. Due to that resulted peculiarities make aerial photographs, carrying out digital aerial triangulation, renewing the topographical plan. The article deals with the submitted example of the topographic plan exhibiting the renovated railway in the city of Vilnius. The updating has been made on the aerial photograph on 1:4000 scale with the photogrammetric instrument PlaniComp P3. The objects possessing no identification in photogrammetry are measured by means of a geodetic method. The redacting varied objects in a database are drawn with AutoCadsoftware. On the basis of this work it is possible to state that for fast and exact updating of topographic plans a progressive photogrammetric method is recommended. It is advised the edition data base to be made by the same operator who made photogrammetric work. The objects are visible in an aerial photo, but no identifying photogrammetry should be applied locally. Digital, renewed data are necessary for drawing up geo information systems (GIS) of the railway, to be able to make fast decisions of urgent problems. First Published Online: 27 Oct 2010